ИРГЭНИЙ НИЙГМИЙН БАЙГУУЛЛАГЫН АРДЧИЛЛЫН БЭХЖИЛТЭД ҮЗҮҮЛЭХ НӨЛӨӨЛӨЛ, ЧИГ ХАНДЛАГА - Б.Одгэрэл; О.Мөнхжаргал (Politology, 2023)
This article summarizes some of the findings from a study on the influence of civil society organizations on the growth of democracy that was conducted as part of the study "Mongolia’s Political Development Since 1990: Processes, Relationships, and Attitudes". The formation and growth of civil society organizations in Mongolia, their involvement in the consolidation of representative democracy there, the effects of these organizations on the transition to and consolidation of democracy, and their contribution to the further development of democracy are all important topics that need to be covered in this article. On the basis of the research of high level specialists, it was also aimed to identify the elements positively and negatively affecting the growth of civil society.